Internal Differences In The Use Of Land Resources In The Agriculture Of Kashkadarya Region - Navotova D.I (Genius Journals, 2023)
The soil, climate and other natural conditions of Kashkadarya region are a favorable region in the republic for the development of agriculture. Based on this, this article analyzes the use of land resources in the regions, regions and rural districts
Keywords: land resources; soil; region; territory